Implementation Of E-Government Policies Through The Citizen Relation Management (CRM) Information System In Support Of Government Governance In Of The Special Region Jakarta - Mohammad Rizki Adhari Jusal; Nurliah Nurdin; Muhadam Labolo; Rosmery Elsye (PT Publikasiku Academic Solution, 2025)
Jakarta Smart City through CRM application is a bright spot in the industrial revolution 4.0 which is expected to improve public services provided by the DKI Jakarta Provincial Government. However, there are still many people who are not familiar with the CRM application for public service needs, and the government's response in responding to reports from residents is relatively slow. The purpose of this research is to identify the causes or reasons why e-government policies through the Citizen Relation Management (CRM) information system have not been running optimally, and to reconstruct the implementation model of e-government policies through the Citizen Relation Management (CRM) information system so that the implementation of CRM can support public services. This study uses the policy implementation theory proposed by Knill and Tuson (2020). The research method used is qualitative research with a descriptive approach. Data collection techniques are carried out through interviews, observations and documentation. The results of the study indicate that the causes or reasons why e-government policies through the Citizen Relation Management (CRM) information system have not run optimally are the inappropriate choice of policy instruments in the form of a complex policy environment, lack of stakeholder support, and less than optimal sustainability. Lack of clarity in policy design in the form of overlapping policies. Lack of community role in supervision. Lack of clarity in the division of tasks and functions in terms of institutional design. Low administrative capacity includes the availability and adequacy of human and financial resources and the appropriateness of the number of health workers needed. Low social acceptance includes the use of social media by the community, low involvement in policy socialization and communication, and dissatisfaction with the distribution of program benefits. The proposed implementation model integrates policy instruments, policy design, control structure, institutional design, administrative capacity, and social acceptance with a focus on sustainability as an integrating factor.